2024
DOI: 10.1186/s40798-023-00668-3
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Balance Skill Learning in Young and Older Individuals: A Systematic Review and Meta-analysis

Lisanne B. M. Bakker,
Claudine J. C. Lamoth,
Tomas Vetrovsky
et al.

Abstract: Background Despite the increasing number of research studies examining the effects of age on the control of posture, the number of annual fall-related injuries and deaths continues to increase. A better understanding of how old age affects the neural mechanisms of postural control and how countermeasures such as balance training could improve the neural control of posture to reduce falls in older individuals is therefore necessary. The aim of this review is to determine the effects of age on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 92 publications
2
2
0
Order By: Relevance
“…A transfer of dynamic balance training on static balance tasks could not be revealed. This is in accordance with a recent systematic review and meta-analysis by (Bakker et al, 2024) who also reported specificity of balance training with only minimal or no transfer to non-trained motor tasks.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A transfer of dynamic balance training on static balance tasks could not be revealed. This is in accordance with a recent systematic review and meta-analysis by (Bakker et al, 2024) who also reported specificity of balance training with only minimal or no transfer to non-trained motor tasks.…”
Section: Discussionsupporting
confidence: 92%
“…Besides the sensorimotor cortex (particularly the leg area of the primary motor cortex, M1) we alternatively applied a-tDCS to the left DLPFC to examine which target region was more effective in facilitating DBT training relative to a sham condition potential transfer effects to static balance tasks. Results of a recent meta-analysis (Bakker et al, 2024) reported improvement in untrained tasks is minimal and not substantial. We assumed that the application of a-tDCS can facilitate changes in brain networks in targeted brain areas to not only improve motor execution but also top-down executive control.…”
Section: Current Studymentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, we highlight the strong association between cognition and more complex balance tasks such as dynamic balance tasks (Divandari et al, 2023). Additionally, as reported by a recent systematic review and metaanalysis, balance training leads to improvement in transfer tasks almost only when the trained task aligns with the transfer task (Bakker et al, 2024).…”
Section: Discussionsupporting
confidence: 69%